(untitled) (Società e diritti, 2023)
Abstract: First of all, this essay intends to thematize the relationship between dissent, pluralism and democracy, at the time of the primacy of technicians (now more conservative, now liberal ones) and of the government of emergencies (whether real or emphasized). Further on, we are going to ponder on the role played by the new media in shaping the public opinion and the political participation, then on the challenges and contradictions that cross contemporary postindustrial societies characterized by the IT and technological revolution. In closing, we will bear a theoretical and political stance of ours: a return to “a new humanism”, whose outline will be explained in the last paragraph of this work.